Patterns of postcranial ossification and sequence heterochrony in bats: Life histories and developmental trade‐offs. Issue 8 (27th May 2014) - Koyabu, Daisuke; Son, Nguyen Truong
ABSTRACT The recently increased interest in studies on sequence heterochrony has uncovered developmental variation between species. However, how changes in developmental program are related to shifts in life‐history parameters remains largely unsolved. Here we provide the most comprehensive data to date on postcranial ossification sequence of bats and compare them to various boreoeutherian mammals with different locomotive modes. Given that bats are equipped with an elongated manus, we expected to detect characteristic heterochronies particularly related to wing development. Although heterochronies related to wing development were confirmed as predicted, unexpected heterochronies regarding the pedal digits were also found. The timing of ossification onset of pedal phalanges is earlier than other mammals. Particularly, bats deviate from others in that pedal phalanges initiate ossification earlier than manual phalanges. It is known that the foot size of new born bats is close to that of adults, and that it takes several weeks to month until the wing is developed for flight. Given that the foot is required to be firm and stable enough at the time of birth to allow continued attachment to the mother and/or cave walls, we suggest that the accelerated development of the hind foot is linked to their unique life history. Since the forelimb is not mature enough for flight at birth and requires extended postnatal time to be large enough to be fully functional, we postulate that bats invest in earlier development of the hindlimb. We conclud that energy allocation trade‐offs can play a significant role in shaping the evolution of development. J. Exp. Zool. (Mol. Dev. Evol.) 322B: 607–618, 2014. © 2014 Wiley Periodicals, Inc.